ANALISIS PENGARUH WHISTLEBLOWING SYSTEM DAN RAPAT KOMITE AUDIT TERHADAP JUMLAH KECURANGAN - Siregar, Anitaria; Surbakti, Ayu Syahbana (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2019)
This study aims to analyze and provides empirical evidence about the effect of whistleblowing system and audit committee meetings on numbers of fraud on finance companies on the Indonesia Stock Exchange Periode 2013-2017. The data used in this research are secondary data taken from annual reports of finance companies that have a whistleblowing system report, audit committee meetings and a complete number of fraud in the period of 2013-2017. The regression model used in this research is multiple aggression analysis. Data processing in this research was carried out using Statistical Product and Service Solution (SPSS) software version 25. The results of this reseach indicate that the whistleblowing system has a positive effect on the number of frauds, while the audit committee meeting has a negative effect on the number of frauds on financial services companies listed on the Indonesia Stock Exchange period 2013-2017.